SYSTEMATIC TREATMENT OF AMERICAN TRICHILIA (MELIACEAE) - Pennington, Terence D. (Phytotaxa, 2016)
The neotropical species of Trichilia are revised. The last major treatment of the group was published in 1981 and 3500 additional collections are examined for the present study. Eighty-one species are recognized, a key to the species is provided, all names are typified and descriptions of all species are given. Substantial changes to the known distribution patterns are documented for species. Distribution maps of all species are provided. Ten new species and one new subspecies are described.